Profile of MIF in Developing Hippocampus: Association With Cell Proliferation and Neurite Outgrowth - Chai, Xuejun; Zhang, Wei; Li, Lingling; Wu, Yongji; Zhu, Xiaoyan; Zhao, Shanting (Frontiers in Molecular Neuroscience, 2020)
Proinflammatory cytokine macrophage migration inhibitory factor (MIF) is a multi-functional cytokine and has been found involved in many neurological diseases such as Alzheimer’s disease (AD), epilepsy, multiple sclerosis. Previous studies have shown that MIF is expressed in neocortex, hippocampus, hypothalamus, cerebellum, and spinal cord in adult mice. It is expressed by astrocytes and activates microglias in neuroinflammation. Further studies have shown that MIF is detected in mossy fibers of dentate granule cells and in apical dendrites of pyramidal neurons in adult hippocampus. Only NeuroD-positive immature granule neurons but not NeuN-positive mature neurons express MIF. These findings led us eager to know the exact role of MIF in the development of hippocampus. Therefore, we systematically checked the spatial and temporal expression pattern of MIF and characterized MIF-positive cells in hippocampus from mice aged from postnatal day 0 (P0) to 3 months. Our results showed that the lowest level of MIF protein occurred at P7 and mif mRNA increased from P0, reached a peak at P7, stably expressed until P30 before declining dramatically at 3 months. MIF was localized in fibers of GFAP- and BLBP-positive radial glial precursor cells in dentate gyrus (DG). DCX-expressing newly generated neurons were MIF-negative. Inhibition of MIF by MIF antagonist S, R-3-(4- hydroxyphenyl)-4, 5-dihydro-5-isoxazole acetic acid methyl ester (ISO-1) reduced BrdU-positive cells. Interestingly, MIF was expressed by NeuN-positive GABAergic interneurons including parvabumin- and Reelin-expressing cells in the DG. Neither NeuN-positive granule cells nor NeuN-positive pyramidal neurons expressed MIF. In transgenic mice POMC-EGFP-positive immature dentate granule cells and Thy1-EGFP-positive mature granule cells were MIF-negative. Treatment of neuronal cultures with ISO-1 inhibited neurite outgrowth. Therefore, we conclude that MIF might be important for feature maintenance of neural stem cells and neurite outgrowth during hippocampal development.